KONDUKTIVITAS TERMAL PAPAN PARTIKEL SEKAM PADI - Wibowo, Hary; Muhajir, Khairul; Rusianto, Toto; Arbintarso, Ellyawan (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
People have used rice husk as an isolator material to prevent melting block of ice by pour it to the block of ice. Rice husk as particle board have been developed as an alternative of isolator material especially for cold storage. Thermal conductivity was affected by many aspects; one of them is filler solid compression ratio. The value of thermal conductivity in the rice husk particle boards has been researched to thermal conductivity with modified of ASTM C177 method and with different solid comparison are: 6-1, 5-1, 4-1, 3-1 i.e from original thick to final thick. From the different of the value of thermal conductivity which was from every density, it was found that the highest value of the thermal conductivity was obtained on rice husk particle board with the density of 3-1 with the value of thermal conductivity 0,133 w/m°C on heat source 70 watt and 0,103 w/m°C on heat source 80 watt and the lowest value of the thermal conductivity was density with 6-1 with the value of thermal conductivity 0,096 w/m°C on heat source 70 watt and 0,082 w/m°C on heat source 80 watt.